ANALISIS INVESTASI KAPAL KHUSUS ANGKUTAN TERNAK KM CAMARA NUSANTARA I DI INDONESIA - Wijaksani, Titik Triary; Nurmalina, Rita; Burhanuddin, Burhanuddin (Jurnal AGRISEP, 2019)
DKI Jakarta Province is a major consumer area in Indonesia. Due to almost all of the beef demand was supplied from other province and even different islands. One of problems regarding inter-island beef cattle distribution was using cargo ship that has not equipped with special facilities for livestock transportation. Accordingly government make the first investment of livestock vessel namely KM Camara Nusantara (CN) I to smooth livestock distributionto DKI Jakarta Province. The investment cost is very high. Therefore this research is intended to analyze the investment feasibility of livestock vessel KM CN I on nonfinancial aspects, financial and economic analyses. Nonfinansial aspect analysis reviewed from market, technical, management and legal, social economic and culture, and environment aspects. Financial and economic analyses use Cost and Benefit Analysis (CBA) which is economic analyses use shadow price. Nonfinancial aspects analysis indicates that the investment is feasible. Financial analysis show that the investment is not feasible based on NPV<0 for both route scenarios when returning to Tenau without cargo or carrying feed cargo. Meanwhile economic analysis for the livestock vessel, which is returning with feed cargo to Tenau is feasible based on NPV>0, B/C Ratio>1, IRR>discount rate and Payback Periode is 13.11 year.